2019
DOI: 10.1002/nau.24251
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of overactive bladder in Chinese children: A population‐based study

Abstract: Aims: To investigate the prevalence of overactive bladder (OAB) and assess its risk factors in 5-to 14-year-old Chinese children. Methods: A cross-sectional study of OAB prevalence was performed by distributing 11 800 anonymous self-administered questionnaires to parents in five provinces of mainland China from July to October 2018. The questionnaires included questions on sociodemographics, history of urinary tract infection (UTI), lower urinary tract symptoms (LUTS), family history of LUTS, bowel symptoms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
16
1
2
Order By: Relevance
“…A former study by the authors demonstrated that childhood obesity was an independent risk factor for pediatric OAB symptoms (OR 1.97; 95% CI: 1.14-3.40) (14). Similarly, a large scale study in China which was conducted by Xing et al (19) and evaluated 10,133 anonymous questionnaires, disclosed that children with obesity, a history of urinary tract infection, nocturnal enuresis, a family history of LUTSs, constipation, and fecal incontinence, had a significantly higher prevalence of OAB compare with normal children (p < 0.05). Fraga et al (20) conducted a cross-sectional study which included 423 children and adolescents aged 5-17 years.…”
Section: Discussionmentioning
confidence: 87%
“…A former study by the authors demonstrated that childhood obesity was an independent risk factor for pediatric OAB symptoms (OR 1.97; 95% CI: 1.14-3.40) (14). Similarly, a large scale study in China which was conducted by Xing et al (19) and evaluated 10,133 anonymous questionnaires, disclosed that children with obesity, a history of urinary tract infection, nocturnal enuresis, a family history of LUTSs, constipation, and fecal incontinence, had a significantly higher prevalence of OAB compare with normal children (p < 0.05). Fraga et al (20) conducted a cross-sectional study which included 423 children and adolescents aged 5-17 years.…”
Section: Discussionmentioning
confidence: 87%
“…We found a strong correlation of constipation with DV but there are studies in the literature showing the association of LUTS and constipation and also OAB with constipation. According to Dong Xing et al, children with constipation have a higher prevalence of OAB than do normal children, with bowel symptoms being a risk factor related to OAB in children 14 . Results of studies on LUTS show that, by treating constipation alone, LUTS can be improved, for instance, Ji Hyun Kim et al showed that OAB symptoms improved with constipation treatment 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract dysfunction(LUTD) is prevalent in up to 31% of 6-8 year-old children and approximately 5% of adolescents. 1,2 In young adults, the prevalence varies greatly between 2-53% depending on the selected population, type of urinary tract symptoms, severity and measurements used. 3,4 Several studies suggest a link between adult LUTD and childhood urinary incontinence (UI).…”
Section: Introductionmentioning
confidence: 99%